Imidazole‐Based Small Molecules that Promote Neurogenesis in Pluripotent Cells1. (9th July 2014) - Kim, Gun‐Hee; Halder, Debasish; Park, Jinhong; Namkung, Wan; Shin, Injae
Abstract Reported herein are two imidazole‐based small molecules, termed neurodazine (Nz) and neurodazole (Nzl), which induce neuronal differentiation of pluripotent P19 cells. Their ability to induce neurogenesis of P19 cells is comparable to that of retinoic acid. However, Nz and Nzl were found to be more selective neurogenesis inducers than retinoic acid owing to their unique ability to suppress astrocyte differentiation of P19 cells. Our results also show that Nz and Nzl promote production of physiologically active neurons because P19‐cell‐derived neurons induced by these substances have functional glutamate responsiveness. The present study suggests that Nz and Nzl could serve as important chemical tools to induce formation of specific populations of neuronal cell types from pluripotent cells.